Supervision of Deep Learning Supervision of Local Wisdom Based on Love in Elementary Madrasah - Al Aliefa Turrasyid; Ahmad Zainuri (Penerbit Presisi Pustaka, 2025)
In the field of education and teaching, supervisors are needed who can dialogue and foster personal and professional growth so that everyone experiences personal and professional improvement. Comprehensive implementation of deep learning and artificial intelligence (AI) in the administration and supervision system of Islamic education based on the value of love in Madrasah Ibtidaiyah. In the fast-paced digital era, Islamic educational institutions face a major challenge in maintaining a balance between technological advancement and spiritual values. Madrasah Ibtidaiyah as an Islamic-based basic educational institution has a strategic role in instilling the values ​​of compassion, social awareness, and respect for the environment from an early age.